THE WIDESPREAD OF ANTIBIOTIC-RESISTANT BACTERIA AND ITS IMPACT ON MEDICINE - Yunusova Guzal Fayzullayevna (World Scientific Research Journal, 2025)
Annotation: This article comprehensively reviews the relevance, causes of spread, clinical significance, and impact of antibiotic-resistant bacteria (ARB) on the medical field. The research highlights the increasing trend of ARB-related infections and the limitations of existing treatment methods. Strategic approaches and preventive measures to address the problem are proposed based on international experience.